2020
DOI: 10.1590/1414-431x20209288
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA ZEB1-AS1 inhibits high glucose-induced EMT and fibrogenesis by regulating the miR-216a-5p/BMP7 axis in diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is one of the leading causes of mortality in diabetic patients. Long non-coding RNA zinc finger E-box binding homeobox 1 antisense 1 (ZEB1-AS1) plays a crucial role in the development of various diseases, including DN. However, the molecular mechanism of ZEB1-AS1 in DN pathogenesis remains elusive. An in vitro DN model was established by treating HK-2 cells with high glucose (HG). Quantitative polymerase chain reaction (qRT-PCR) was utilized to detect the expression levels of ZEB1-AS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…When expressed, this gene acts as an oncogenic regulator in many human tumors (Ni et al, 2020). Meng and Zhai (2020) demonstrated that ZEB1-AS1 overexpression inhibits HG-induced RF by suppressing EMT and fibrogenesis. Mechanistically, they identified that ZEB1-AS1 impedes RF by regulating BMP7 expression and inhibits EMT of HK-2 cells by competitively binding to miR-216a-5p (Meng and Zhai, 2020).…”
Section: Lncrna Zeb1-as1mentioning
confidence: 99%
“…When expressed, this gene acts as an oncogenic regulator in many human tumors (Ni et al, 2020). Meng and Zhai (2020) demonstrated that ZEB1-AS1 overexpression inhibits HG-induced RF by suppressing EMT and fibrogenesis. Mechanistically, they identified that ZEB1-AS1 impedes RF by regulating BMP7 expression and inhibits EMT of HK-2 cells by competitively binding to miR-216a-5p (Meng and Zhai, 2020).…”
Section: Lncrna Zeb1-as1mentioning
confidence: 99%
“…LncRNA zinc finger E-box binding homeobox 1 antisense 1 (ZEB1-AS1) plays a protective role in DKD by targeting profibrotic miR-216a-5p to inhibit HK-induced EMT and renal fibrosis. Besides, the anti-fibrotic function of ZEB1-AS1 is also verified that it may bind to H3K4 methyltransferase myeloid and lymphoid or mixed-lineage leukemia 1 (MLL1) and p53 in patients with DKD ( Wang et al, 2018a ; Meng et al, 2020 ). lncRNA NR_038323 exerts an anti-fibrotic effect by interacting with miR-324-3p.…”
Section: The Emerging Role Of Non-coding Rnas In Dkdmentioning
confidence: 87%
“…NRP-1 undergoes upregulation in PCa cells, resulting in proliferation and malignancy ( Figure 11 ) [ 216 , 217 ]. Additionally, zinc finger E-box binding homeobox 1 (ZEB1) is an upstream mediator of EMT and contributes to the metastasis and invasion of cancer cells via the induction of EMT [ 218 , 219 ]. Accumulating data demonstrate that ZEB1 has high expression in PCa cancer cells and is correlated with the progression and metastasis of these cancer cells [ 220 , 221 ].…”
Section: Nano-vehiclesmentioning
confidence: 99%